National Culture, IPSAS Adoption, and Economic Development: A Cross-Country Analysis - Khaghaany , Maithm; Najm, Karar Jasim; Rajeeb, Wisam Neamah; Almagtome, Akeel Hamza (Journal of Ecohumanism, 2024)
The study examines the relationship between the dimensions of national culture at the country level, measured by Hofstede’s framework, IPSAS adoption, and a country’s economic development levels. It uses a quantitative analysis method for a sample of 95 countries over ten years (2014-2023). The analysis using linear correlation analysis and multiple regression analysis of variables reveals a statistically significant relationship between three national cultural factors and the adoption of reporting standards for public sector units at the state level. The national culture factors of power distance, uncertainty avoidance, and individualism significantly affect the adoption of IPSAS. Meanwhile, the relationships between masculinity, long-term orientation, indulgence, and the adoption of IPSAS were insignificant. The results also show that adopting IPSAS contributes directly to enhancing economic development at the country level by supporting transparency and enhancing investor confidence in the national economy. The results also show a significant relationship between four national cultural factors and the level of economic development at the country level. This study provides a better understanding of the impact of the society’s cultural background in achieving sustainable economic development through adopting measures that support economic development plans and attracting foreign investment. In addition, the current study provides a basis for accounting policymakers at the state level to identify the determinants of the transition toward adopting international financial reporting standards for public sector units. Our results also help economic policymakers in developing countries formulate economic policies in line with the country’s cultural environment to enable them to achieve the desired goals.